Effect Of Placement And Work Environment On Work Discipline And Their Impact On Performance Of Employee Office Jati Karya Village, Binjai City - Putra, Suria Alamsyah (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2021)
The purpose of this study was to analyze the direct effect of placement on the work discipline of the employees of the Jati Karya Sub-District Office, Binjai City. The research design in this research method includes explanatory research, which explains the causal relationship between the variables in the study. In conclusion, placement has a positive and insignificant effect on work discipline. These results indicate that better placement will not necessarily increase work discipline at the Jati Karya Sub-District Office, Binjai City. Work discipline in this study is influenced by placement through orientation / introduction, suitability of interests with work, suitability of abilities with work, suitability of knowledge with work, and knowledge possessed in accordance with work can improve work discipline in terms of complying with company regulations, working effectively, accept corrections, be present always on time and try to complete the work on time.